Cankar kot utemeljitelj profesionalnega pisatelja - umetnika - Dović, Marijan (Slavistična revija, 2006)
The article discusses from the systemic-theoretical point of view Ivan Cankar's efforts to establish a new model of the Slovene literary writer, which he calls writer-artist, and for his professionalization. The artistic model has remained essential for Slovene literary author's (self)understanding until the present and it also affected the specific understanding of the literary intermediaries in Slovenia.
Keywords: Cankar, Ivan, 1876-1918; literarni sistem; literary system; moderna; Moderna Therapeutics; publishing; Slovene literature; Slovene writers; slovenska književnost; slovenski pisatelji; založništvo